Assessing Mediating Effect of Motivation Types on Competition Intervention For Physically Inactive Adults - Fadli, Fatmawati; Prestwich, Andrew; Sykes-Muskett, Bianca (Jurnal Ilmiah Peuradeun, 2018)
Competition has been widely used as the behaviour change technique for physical activity intervention, this approach might push someone motivation to achieve the desired behaviour. Therefore, the objective of this study was to assess the mediating effects of the motivation on the competition intervention effectiveness. An experimental research was conducted where participants were randomly allocated into one of two groups (control and competition group). For calculating the motivation types, Behavioural Regulation in Exercise Questionnaire was administered. The results revealed that motivation was not found to mediate the effect of competition intervention.